The course delivery process in LMS - Regina Kulvietienė; Jelena Stankevič; Irma Šileikienė (Lietuvos Matematikos Rinkinys)
Learning management systems (LMS) characterized by component architecture base on learning technology standards. Therefore, e-learning content can be developed by using different standalone authoring tools or repurposed from other applications content. SCORM and AICC are most popular standards. Requirements for SCORM e-learning components can be stated as: durability, accessibility, interoperability and reusability, therefore content standards include places for learning object metadata. Package includes content, metadata about the content, metadata about the course, and the course structure.